1985
DOI: 10.1149/1.2114180
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical and Spectroscopic Studies of Sulfur in Aluminum Chloride‐N‐(n‐Butyl)Pyridinium Chloride

Abstract: The behavior of sulfur in aluminum chloride-N-(n-butyl)p_y_ridinium chloride (A1C13-BPC) was studied using Raman spectroscopy and electrochemical techniques. In basic (BPC-rich) melts, sulfur can be reduced to sulfide, probably in the form of an A1SCl-like species. No oxidation to positive oxidation states of sulfur is observed in basic melts. In acidic (A1C13-rich) melts, sulfur can be oxidized to S(I) and eventually to S(IV), which is only stable in the melt for short periods of time. No reduction to sulfide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 24 publications
1
31
1
Order By: Relevance
“…As described in the literature, sulfur species was oxidized from S(I) to S(IV) at a potential range of 2.11-2.28 V (vs. Al) (i. e., voltage of 2.11-2.28 V for an AlÀ S cell). [27] The reduction reaction (from S(IV) to S) was proceeded at 1.89-1.49 V (vs. Al). [27] Then the S could be further reduced to Al 2 S 3 .…”
Section: Using An Alcl 3 /Urea Ionic Liquid Analog Electrolyte For Immentioning
confidence: 99%
See 2 more Smart Citations
“…As described in the literature, sulfur species was oxidized from S(I) to S(IV) at a potential range of 2.11-2.28 V (vs. Al) (i. e., voltage of 2.11-2.28 V for an AlÀ S cell). [27] The reduction reaction (from S(IV) to S) was proceeded at 1.89-1.49 V (vs. Al). [27] Then the S could be further reduced to Al 2 S 3 .…”
Section: Using An Alcl 3 /Urea Ionic Liquid Analog Electrolyte For Immentioning
confidence: 99%
“…[27] The reduction reaction (from S(IV) to S) was proceeded at 1.89-1.49 V (vs. Al). [27] Then the S could be further reduced to Al 2 S 3 . [22,24] The suggested reactions of the electrodesare shown in Equations (1-3): [22,24,26,27] Anode:…”
Section: Using An Alcl 3 /Urea Ionic Liquid Analog Electrolyte For Immentioning
confidence: 99%
See 1 more Smart Citation
“…Withinh ours, the substance decomposese ven under inert conditions and at low temperatures. In contrast, all hydrosulfide and hydroselenide salts form room-temperature and long-term stable substances.A fter purification and storage at ambient temperature under inert conditions, the imidazolium, pyrrolidinium, and phosphonium hydrosulfides and selenides stayed unchanged over ap eriod of severalm onths.W ith exception of [nBu 3 MeP][HS] (5), which is ah ighly viscous oil, all compounds were isolated as almost colorlesss olids. In most cases, elemental analysisy ielded good to satisfactory results after recrystallization.…”
Section: Synthesis Of Hydrochalcogenide Saltsmentioning
confidence: 99%
“…[2] Reports concerningt he general characteristics of sulfur in ionic liquids, whicha re of uttermost importance for the understanding and optimization of lithium sulfur batteries are scarce, though. The electrochemistry of sulfur was investigated in n-butyl-pyridinium tetrachloroaluminate several decades ago [3] and Manan et al more recently reported detailed electrochemical studies of sulfur and sodium polysulfides in 1-butyl-3-methylimidazolium dicyanamide. [4] The solubility of chalcogens and phosphorus in av arietyo fi onicl iquids comprising tosylate, bistriflimide, dithiocarbamate, and di-and trithiocarbonatea nions was investigated by Seddon and coworkers.…”
Section: Introductionmentioning
confidence: 99%